2012
DOI: 10.1002/jlcr.2910
|View full text |Cite
|
Sign up to set email alerts
|

177Lu‐labeled monomeric, dimeric and multimeric RGD peptides for the therapy of tumors expressing α(ν)β(3) integrins

Abstract: The conjugation of peptides to gold nanoparticles (AuNPs) produces biocompatible and stable multimeric systems with target-specific molecular recognition. Peptides based on the cyclic Arg-Gly-Asp (RGD) sequence have been reported as high-affinity agents for the a(n)b(3) integrin. The aim of this research was to prepare a multimeric system of 177 Lu-labeled gold nanoparticles conjugated to c(RGDfK)C (cyclo(Arg-Gly-Asp-Phe-Lys)Cys) and to compare the radiation-absorbed dose with that of 177 Lu-labeled monomeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…Considering that one Becquerel (Bq) of Lu-177 produces 841558 disintegrations until total decay (total disintegrations = ∫ 0 ( ) ) with a maximum − -particle energy of 0.498 MeV, it is expected that, with the high 177 Lu-DenAuNPfolate-bombesin retention observed in tumors, the total radiation absorbed dose to the malignant tissue could easily reach 2 Gy per MBq [33]. However, further preclinical studies must 10 Journal of Nanomaterials be carried out in order to evaluate the toxicity, biokinetics, and dosimetry of this radiopharmaceutical.…”
Section: T47d Cancer Cell Studies Preliminary Cell Studiesmentioning
confidence: 99%
“…Considering that one Becquerel (Bq) of Lu-177 produces 841558 disintegrations until total decay (total disintegrations = ∫ 0 ( ) ) with a maximum − -particle energy of 0.498 MeV, it is expected that, with the high 177 Lu-DenAuNPfolate-bombesin retention observed in tumors, the total radiation absorbed dose to the malignant tissue could easily reach 2 Gy per MBq [33]. However, further preclinical studies must 10 Journal of Nanomaterials be carried out in order to evaluate the toxicity, biokinetics, and dosimetry of this radiopharmaceutical.…”
Section: T47d Cancer Cell Studies Preliminary Cell Studiesmentioning
confidence: 99%
“…Before laser irradiation, the chemical conjugation was confirmed by UV-Vis, medium-and far-IR, Raman spectroscopy, and Transmission Electron Microscopy (TEM), as previously reported [16,19].…”
Section: Characterization Before and After Laser Irradiationmentioning
confidence: 63%
“…This shifting is attributed to the changes in the refraction index as a consequence of the interaction between the peptide and the AuNP surface [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,15,17,18,21,24,27,33,39,45,46,49,53,[78][79][80][81][82] These were largely adopted for calculation of organ absorbed dose and dosimetry of radionuclide-labeled compounds in preclinical experiments. [83][84][85][86][87][88][89][90][91][92][93][94][95] These computational models were also integrated in comparative Monte Carlo-based simulations studies investigating patterns of uptake and biodistribution data of radiopharmaceuticals for the purpose of dose estimation in molecular radiotherapy and diagnostic nuclear medical imaging procedures. [96][97][98][99][100][101][102][103][104][105][106][107] For external exposure to ionizing radiation, few studies reported on the calculation of organ dose conversion coefficients for small animals under ideal irradiation conditions (left lateral, right lateral, dorsal-ventral, ventral-dorsal, and isotropic irradiation directions), …”
Section: A Ionizing Radiation Dosimetrymentioning
confidence: 99%